Aeromonas schubertii, a novel bacterium recovered from AHPND affected farm is lethal to whiteleg shrimp, Penaeus vannamei. (December 2020) - Sangpo, Pattiya; Thitamadee, Siripong; Dong, Ha Thanh; Senapin, Saengchan
Abstract: Retrospective diagnosis of a bacterial collection (n = 31) originated from five farms reportedly affected by early mortality syndrome (EMS) in Southeast Asia in 2016 revealed that 9/31 isolates from two farms tested positive for V. parahaemolyticus causing acute hepatopancreatic necrosis disease (VPAHPND ). Molecular analysis of the 22 remaining isolates showed that 21 isolates belong to Vibrio species including VPnon-AHPND, V. vulnificus, V. cholerae, V. owensii and V. alginolyticus . One isolate from an AHPND farm was preliminarily identified as Aeromonas schubertii based on 99.43% nucleotide identity of 16S rRNA to the reference strain ATCC 43700 (X60416). Diseases caused by Vibrio bacteria have been well-studied in shrimp while pathogenic potential of non- Vibrio species has been relatively overlooked. Since the description of A. schubertii present in shrimp farms is rare, this study therefore focused on species identification and its pathogenic potential to shrimp based on a combination of multiple approaches i.e. multilocus sequence analysis (MLSA), challenge test, histopathology and in situ hybridization (ISH). Based on MLSA of 2464 bp derived from 16S rRNA (1346 bp), gyrB (568 bp) and rpoB (550 bp), this isolate was confirmed as A. schubertii . Immersion challenge using three successive 10-fold serial dilutions (2 × 10 4 to 2 × 10 6 CFU/mL) revealed that A. schubertii was pathogenic to shrimp and cumulative mortalities were dose-dependent (45–70%). The diseased shrimp exhibited gross sign of reddish body and remarkable histopathological lesion of collapsed hepatopancreatic tubules and typical encapsulation. ISH using A. schubertii -specific probe confirmed localization of bacteria in the hepatopancreas of the infected shrimp. In summary, this study reported a novel pathogenic, non- Vibrio species, A. schubertii recovered from an AHPND-affected farm causing up to 70% mortality in immersion challenge. Since A. schubertii is relatively new to shrimp, this may pose a potential risk for low salinity shrimp farming areas, active surveillance of this pathogen, therefore, should not be overlooked. Highlights: Retrospective diagnosis of an archived bacterial collection was performed in this study. A novel bacterium Aeromonas schubertii associated with an AHPND affected farm was revealed. A. schubertii is lethal to shrimp, which caused 45-70% mortality in an immersion challenge. The bacterial infection caused collapsed epithelial cells of the hepatopancreatic tubules and typical encapsulation.